2009
DOI: 10.1111/j.1475-1313.2009.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

A versatile optoelectronic aid for low vision patients

Abstract: The purpose of this work is to describe a versatile optoelectronic aid for low vision rehabilitation based on reconfigurable hardware. This aid is easily adaptable to diverse pathologies (with different associated processing tasks) and to the progression of the visual impairment. This platform has a mobile configuration that uses a see-through head-mounted display (Nomad). We have implemented different types of vision enhancement on this versatile platform, and briefly summarize here their computational costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…Since then, technological advances have made head-mounted displays lighter and smaller, with more processing power, and a performance comparison with conventional optical devices indicated that their greater magnification range significantly improved utility at long and intermediate distances. 10 , 14 In addition, Peterson et al 15 showed that reading with a conventional optical aid, such as a magnifier, was slower than with head-mounted displays. Furthermore, previous research has indicated that head-mounted displays have the potential to improve visual search and nighttime travel in individuals with visual field loss and impaired dark adaptation, by virtue of automatic gain control, variable object magnification, and the ability to magnify/minify sections of the visual field.…”
mentioning
confidence: 99%
“…Since then, technological advances have made head-mounted displays lighter and smaller, with more processing power, and a performance comparison with conventional optical devices indicated that their greater magnification range significantly improved utility at long and intermediate distances. 10 , 14 In addition, Peterson et al 15 showed that reading with a conventional optical aid, such as a magnifier, was slower than with head-mounted displays. Furthermore, previous research has indicated that head-mounted displays have the potential to improve visual search and nighttime travel in individuals with visual field loss and impaired dark adaptation, by virtue of automatic gain control, variable object magnification, and the ability to magnify/minify sections of the visual field.…”
mentioning
confidence: 99%
“…Minification has been used to expand of the VF of participants with RP and PFL by 2 to 4 times. 54,66,67 Overlaying a minified contour image, using a multiplexing approach, did not reduce VA and CS in one study 67 but did in another where the minified image was a grayscale. 54 Comparing performance with and without HMDs, minification using grayscale images did not significantly improve mobility in an obstacle-free course under very dim conditions (< 0.1 lux) in people with night blindness and PFL.…”
Section: Minificationmentioning
confidence: 96%
“…Expanding VF size is potentially useful as it is an important predictor of mobility performance. [13][14][15] Eight studies, 54,[66][67][68][69][70][71][72] summarized in Appendix Table A2, assessed the effects of minification on orientation and mobility.…”
Section: Minificationmentioning
confidence: 99%
See 1 more Smart Citation
“…HMD has become more prevalent in recent years but the first head-mounted LVA, the Low Vision Enhancement System, was in fact developed over 20 years ago 10 and improved patients’ contrast sensitivity, acuity and illumination; 8 however, this device was heavy and functioned too slowly for routine use. 8 Modern electronic HMDs have been shown to improve constricted peripheral fields, 4,6,9 night vision 6 and visual acuity, 7 though their effectiveness compared to standard LVAs has not been adequately studied. 8 Here, we present an overview of the shortcomings of currently available LVAs; describe the various types of HMD that currently exist; review the optical and human factors considerations relevant to the use of HMD in low vision; and suggest a lexicon to standardize future discussions and evaluations of HMD technologies in vision research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%